The Representation of Narcissistic Personality Disorder of Baroness in the Movie of “Cruella” Directed by Craig Gillespie - Mukhlasul Fasikh; Dia Maelani; Abdul Muhid Murtadho (STIBA IEC JAKARTA, 2024)
The purposes of this research are: (1) To examine the character of Narcissistic Personality Disorder on Baroness (2) To show the impacts of Baroness’s Narcissistic Personality Disorder to people around her. This research found out the characterization of Narcissistic Personality Disorder on Baroness the villain on Cruella (2021) movie. In studying of Narcissistic Personality Disorder, the researchers use Qualitative research methodology and use psychological approach to examine the psychology aspect on Baroness. This research also uses two main books from American Psychiatry Association DSM – V to know the characterization of Narcissistic Personality Disorder and book The Everything : Guide to Narcissistic Personality Disorder by Goodman, Lechan Cynthia and Leff, Barbara to describe the impact of Baroness’s Narcissistic Personality Disorder to people around her. The researchers found the significant characterization which is the Grandiose of Self – Importance on Baroness’s Narcissistic Personality Disorder and the significant impacts are Narcissistic as Co – Worker and Narcissistic as Boss.